Unmet needs and prospects for oritavancin in the management of vancomycin-resistant enterococcal infections (2012)
The treatment of infections caused by vancomycin-resistant enterococci (VRE) has become an important clinical challenge and compromises the care of critically ill patients. A striking increase in the frequency of nosocomial isolation of multidrug-resistant Enterococcus faecium has dramatically reduced the therapeutic alternatives because the majority of E. faecium isolates are resistant to ampicillin and vancomycin. Only 2 agents have US Food and Drug Administration approval for the treatment of VRE (E. faecium) infections, namely, linezolid and quinupristin/dalfopristin (Q/D). However, the use of these compounds in severe VRE infections is hampered by the lack of in vivo bactericidal activity, reports of therapeutic failures with monotherapy, a requirement for central venous access for administration (Q/D), and adverse-effect profile. The lipopeptide antimicrobial daptomycin has in vitro bactericidal activity against VRE; however, clinical use of this compound for VRE has not been well studied, and the reports of resistance emerging during therapy at the approved doses are worrisome. Tigecycline has in vitro bacteriostatic activity against VRE, but its clinical use for serious enterococcal infections is unclear due to low serum levels and static effect. Thus, current reliable therapies for VRE appear to be limited, and clinical data that use the above compounds are certainly scant. Oritavancin is an investigational semisynthetic glycopeptide with potent in vitro activity against VRE (both VanA and VanB phenotypes). Although review of the available preclinical data indicates that this compound used as a single agent is likely to have important limitations for the treatment of a severe VRE infection (ie, endocarditis), combination of oritavancin with other agents such as aminoglycosides may offer promise and deserves further investigation, as does use of oritavancin for less serious infections as monotherapy for vancomycin-susceptible and multidrug-resistant enterococci.